Early-Stage Ruptured Hepatocellular Carcinoma With Different Tumor Diameters: Small Tumors Have a Better Prognosis - Xia, Feng; Huang, Zhiyuan; Zhang, Qiao; Ndhlovu, Elijah; Zhang, Mingyu; Chen, Xiaoping; Zhang, Bixiang; Zhu, Peng (Frontiers in Oncology, 2022)
Abstract Background and aim： Ruptured hepatocellular carcinoma(rHCC) is classified as T4 according to the TNM staging system with a very poor(does not achieve expected) prognosis, which has always been controversial. This study aimed to assess the specific impact of different tumor diameters on the post-treatment prognosis of BCLC stage 0/A rHCC patients. Methods: Data from 258 patients with BCLC stage 0/A HCC treated in our center from January 2008 to December 2017 was collected, including 143 rHCC patients and 115 patients with non-ruptured HCC(nrHCC). With the help of X-tile software, we determined the cutoff value of the tumor diameter in patients with rHCC. Using 8 cm as the cutoff, we divided rHCC patients into Small-rHCC (n = 96) and Large-rHCC (n = 47) groups, compared the prognoses of the S-rHCC and L-rHCC group, as well as the prognoses of the two groups with the nrHCC group using the Kaplan-Meier method, and screened the prognostic factors of rHCC patients using multivariate Cox risk model. Results: The OS of the S-rHCC group was significantly higher than that of the L-rHCC group (HR = 2.41 [1.60 – 3.63]), and the OS of the nrHCC group was comparable to that of the S-rHCC group (P = 0.204). In patients treated with surgery only, OS and RFS were also comparable in the S-rHCC nrHCC group. Meanwhile, multivariate Cox regression analysis revealed that alpha-fetoprotein (AFP), alkaline phosphatase (ALP), and main method of treatment were also prognostic factors for OS in patients with rHCC. Conclusions: Ruptured HCC with a relatively small diameter (≤ 8 cm) can also achieve the same prognosis as nrHCC patients after aggressive treatment. It is also not recommended to include all patients with rHCC in stage T4.